Thermal demands and its interactions with environmental factors account for national-level variation in aggression - Guo, Qingke; Li, Sisi; Shen, Jinkun; Lu, Jianli (Frontiers in Psychology, 2022)
Abstract: Literature shows that psychological phenomena, including values (e.g., individualism vs. collectivism), personality, and behaviors (e.g., prosocial and aggressive behavior), are geographically clustered. The effects of temperature on interpersonal and intergroup aggression have been studied by many social psychologists. To date the interactions between temperature and other geographical factors have not been addressed. This study is aiming to examine the effects of thermal demands and the moderating effects of natural geographical factors on aggressive behavior at national level. Data for 156 countries was obtained from publicly available databases. Consistent with the life-history theory, results of this study showed that aggressive behavior has a positive relation with heat demands, and a negative relation with cold demands. Aggressive behavior was also positively correlated with sunlight and altitude, and negatively correlated with coastline vicinity. Forest, coastline vicinity, and rainfall moderated the effect of thermal demands on aggressive behavior. In countries with more forests, with more rainfall, and closer to coastline, the negative effects of cold demands on aggressive behavior were stronger.